The bacterial enhancer-dependent RNA polymerase - Zhang,N; Darbari,VC; Glyde,R; Zhang,X; Buck,M (Biochemical Journal, 2016)
Transcription initiation is highly regulated in bacterial cells, allowing adaptive gene regulation in response to environment cues. One class of promoter specificity factor called sigma54 enables such adaptive gene expression through its ability to lock the RNA polymerase down into a state unable to melt out promoter DNA for transcription initiation. Promoter DNA opening then occurs through the action of specialized transcription control proteins called bacterial enhancer-binding proteins (bEBPs) that remodel the sigma54 factor within the closed promoter complexes. The remodelling of sigma54 occurs through an ATP-binding and hydrolysis reaction carried out by the bEBPs. The regulation of bEBP self-assembly into typically homomeric hexamers allows regulated gene expression since the self-assembly is required for bEBP ATPase activity and its direct engagement with the sigma54 factor during the remodelling reaction. Crystallographic studies have now established that in the closed promoter complex, the sigma54 factor occupies the bacterial RNA polymerase in ways that will physically impede promoter DNA opening and the loading of melted out promoter DNA into the DNA-binding clefts of the RNA polymerase. Large-scale structural re-organizations of sigma54 require contact of the bEBP with an amino-terminal glutamine and leucine-rich sequence of sigma54, and lead to domain movements within the core RNA polymerase necessary for making open promoter complexes and synthesizing the nascent RNA transcript.